IoT-Based Plant Growth Monitoring System - Mohan, Saymaharan; Arbaiy, Nureize (Applied Information Technology And Computer Science, 2025)
Impatiens flowers require frequent maintenance due to their preference for shady weather. An Internet of Things (IoT)-Based Plant Growth Monitoring System can maximize productivity, minimize human labor, and provide real-time data to improve plant growth. Due to their meticulous temperature, humidity, light, and water requirements, Impatiens flowers have been used as a case study to develop an automated growth monitoring system. Currently, visual inspection methods are used to monitor plant development. However, this method has limited the capacity for decision-making, especially during unexpected weather fluctuations. Furthermore, operational efficiency can be compromised by the absence of a computerized record-keeping system. An Internet of Things (IoT)-Based Plant Growth Monitoring System is proposed to overcome these difficulties, which can monitor environmental variables using sensors. DHT11 sensors for temperature and humidity monitoring, soil moisture sensors for controlling watering requirements, light sensors for optimal light exposure, and raindrop sensors for rainfall monitoring from the system. Real-time data collection will increase production, save water consumption, and improve plant care. PHP programming and Agile approach are used in the system development for this project. By using this technology, data-driven decision-making will become easier, plant health will be improved, and high-quality services will be provided while encouraging sustainable behavior and reducing environmental impact.